Infant Massage and Quality of Early Mother–Infant Interactions: Are There Associations with Maternal Psychological Wellbeing, Marital Quality, and Social Support? - Porreca, Alessio; Parolin, Micol; Bozza, Giusy; Freato, Susanna; Simonelli, Alessandra (Frontiers in Psychology, 2017)
Infant massage programs have proved to be effective in enhancing post-natal development of highly risk infants such as preterm newborns and drug or HIV exposed children. Less studies have focused on the role of infant massage in sustaining the co-construction of early adult-child relationships. In line with this lack of literature, the present paper reports on a pilot study aimed at investigating longitudinally the quality of mother-child interactions, with specific reference to Emotional Availability (EA), in a group of mother-child pairs involved in infant massage classes. Moreover, associations between mother-child EA, maternal wellbeing, marital adjustment and social support were also investigated, with the hypothesis to find a link between low maternal distress, high couple satisfaction and high perceived support and interactions of better quality in the dyads. The study involved 20 mothers and their children, aged between 2 and 7 months, who participated to infant massage classes. The assessment took place at 3 stages: at the beginning of massage course, at the end of it and at 1-month follow-up. At the first stage of assessment self-report questionnaires were administered to examine the presence of maternal psychiatric symptoms (SCL-90-R), perceived social support (MSPSS) and marital adjustment (Dyadic Adjustment Scale); dyadic interactions were observed and rated with the Emotional Availability Scales (EAS-Biringen, 2008) at each stage of data collection. The results showed a significant improvement in the quality of mother-child interactions, between the first and the last evaluation, parallel to the unfolding of the massage program, highlighting a general increase in maternal and child’s EA. The presence of maternal psychological distress resulted associated with less optimal mother-child emotional exchanges, while the hypothesis regarding couple satisfaction and social support influence were not confirmed. These preliminary results, if replicated, seem to sustain the usefulness of infant massage and the importance of focusing on early mother-infant interactions.